1995
DOI: 10.1099/13500872-141-11-2955
|View full text |Cite
|
Sign up to set email alerts
|

A high cell wall negative charge is necessary for the growth of the alkaliphile Bacillus lentus C-125 at elevated pH

Abstract: The structural components in cell walls of three mutants of a facultative alkaliphile, Bacillus lentus C-125, defective in certain cell-wall components were characterized in detail. The cell walls of the wild-type C-125 were thick and increased in thickness when grown at high pH. Electron microscopy showed that triple layers developed when the bacteria were grown in an alkaline environment. In contrast, cell walls of teichuronopeptide (1UP)-defective mutants consisted of a single layer. For both the wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The role of the B. pseudofirmus OF4 SlpA in alkaliphily is somewhat analogous to that proposed for the cell wall teichuronopeptide in B. halodurans C-125 (3)(4)(5)21). Neither of these cell wall polymers in the two different alkaliphiles is essential for alkaliphily, but both are involved in supporting the Na ϩ -dependent pH homeostasis that principally relies upon active transport mechanisms.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The role of the B. pseudofirmus OF4 SlpA in alkaliphily is somewhat analogous to that proposed for the cell wall teichuronopeptide in B. halodurans C-125 (3)(4)(5)21). Neither of these cell wall polymers in the two different alkaliphiles is essential for alkaliphily, but both are involved in supporting the Na ϩ -dependent pH homeostasis that principally relies upon active transport mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…Net proton as well as solute uptake is coupled to this cycle. Work on B. halodurans C-125 has shown that in addition to the critical role of the active transporters of the Na ϩ cycle, acidic cell surface polymers contribute to pH homeostasis and alkaliphily, in particular a teichuronopeptide that is more highly expressed at high pH then at low pH (3)(4)(5). By contrast, B. pseudofirmus OF4 did not appear to possess these acidic polymers (18).…”
mentioning
confidence: 99%
“…It is reported that the amount of acidic polymers increases during growth under alkaline pH conditions. 16) A pH-homeostatic mechanism for alkaliphilic bacteria has been proposed taking the important role of anionic polymer layer in their cell walls into account. Donnan equilibria in the bacterial cell walls were calculated to estimate the pH values inside the polymer layer of the cell walls when the outer aqueous solution is in alkaline nature.…”
Section: )mentioning
confidence: 99%
“…At this pH, C-125 grows well and develops the homeostatic activity well although C-125-90 grows poorly. 15,17) The cytoplasmic pH of each derivative exposed to pH lower than 9 was almost the same as that of the parent (Fig. 1).…”
Section: )mentioning
confidence: 81%
“…Cell-wall densities of negatively charged compounds, such as glutamic and glucuronic acids, are 6.7, 6.0, 4.0 and 4.1 mmol W mg of peptidoglycan in C-125, C-125-11, C-125-F19 and C-125-90 grown at pH 10, respectively. 17) Thus, it is likely that the intensity of the pHhomeostatic activity and abundance of the acidic constituents are correlated in the cells grown at pH 10.…”
Section: )mentioning
confidence: 99%